Effects of Climate Change induced electricity load shedding on small holder agricultural enterprises in Zambia: The case of Five Southern Province Districts - Siankwilimba, Enock (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Zambia is currently facing electricity shortages, which affect the power supply throughout the country. Load shedding and power outages have had effects on agricultural subsectors, industries and household food security with negative implications for the productivity of the country‘s economy. This paper analyses the effects of climate change induced electricity power load shedding on smallholder farmers‘ agricultural productivity and production in Mazabuka, Monze, Choma, Kalomo and Namwala districts of Southern Province of Zambia for the 12 months period starting February 2015 through to February 2016 . To gather the information needed to understand the effects and extent of load shedding and also determine whether there were differential outcomes on various enterprises, 149 structured sets of questionnaires were administered at enterprise level comprising of Dairy, Abattoir (beef), Crop irrigation, Feedlot and Poultry. Furthermore, to broaden and deepen the understanding of the effects and extent of load shedding on smallholder farmers, 17 focus group discussions were conducted with a total of 203 farmers from the same studied enterprises. Although ZESCO had released load shedding time tables for each district and for each different feeder, the study reveals that some enterprises in sample area were apparently either not aware of the scheduled power cuts or ZESCO had failed to follow their programmed load shedding time table. The findings show that Monze and Namwala respectively started experiencing power cuts as early as February 2015 and March, 2015, and were the top two districts having abrupt power cuts. Many enterprises experienced reduction in the estimated average level of production during load shedding. The production level reduced by 26.6% for cattle slaughtered in abattoirs, 19.3% for steers raised for market in feedlots, 13.5% for chickens raised for market in poultry and 34.7% for quantity of milk produced in dairy (milk collection centers). On the contrary, the quantity of irrigated crop harvested increased by 18.6% during load shedding. The effects and extent of load shedding was profound in the extra costs incurred to sustain operations of the enterprise. More than half (64.71%) of Non sole proprietors (compared to Sole proprietorship (45.26%) agree to incur more costs due to power cuts. Further, there were delivery delays from suppliers (46.3%) and to customers (46.3%) due to load shedding. As they try to adapt and mitigate the effects of load shedding on the operation of the enterprise, majority of Sole proprietorship (49.47%) and 46.15% of Non-Sole proprietorship often times reduce the expansion of the enterprise. It is also significant that stocking and use of charcoal/firewood during load shedding was often used by Sole proprietorship (61.7%) compared to 26.92% of Non-Sole proprietorship. Similarly the majority Sole proprietorship (85.26%) and Non-Sole proprietorship ( 75%) resorted to renting alternative tools/equipment to back up power during load shedding, while the highest proportion of Non-Sole proprietorship (69.23%) often resort to buying alternative tools/equipments to back up power supply. Of the assets bought/rented in as alternative power sources, charcoal/breezier became very common among the poultry enterprise while generators were common among dairy, abattoir and feedlot.